2017
DOI: 10.2135/cropsci2016.10.0849
|View full text |Cite
|
Sign up to set email alerts
|

The US National Mall Microbiome: A Census of Rhizosphere Bacteria Inhabiting Landscape Turf

Abstract: A groecosystems are increasingly at risk due to the movement of nonindigenous microorganisms into new environments (Waage and Mumford, 2008). More than half of all documented plant pathogen invasions are directly attributable to humanmediated transfer of nonindigenous microorganisms (Anderson et al., 2004). It is generally accepted that heightened levels of microbial invasions in recent years are correlated with intensified globalization, specifically due to growing levels of world trade in agricultural commod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
(47 reference statements)
1
18
0
Order By: Relevance
“…Schedonorus phoenix (Scop.)] and P. pratensis L., the soil microbiome was compared pre-and postrenovation with the originating sod farm (Crouch et al, 2017). Bacterial 16S rRNA sequencing revealed that across all four lawns in the study, the Gram-negative, Proteobacteria phylum was 52.2-58.6% of the observed sequences, of which the genus Rhodoplanes was widely abundant (26.4-37.3%).…”
Section: Plant Species Compositionmentioning
confidence: 99%
See 3 more Smart Citations
“…Schedonorus phoenix (Scop.)] and P. pratensis L., the soil microbiome was compared pre-and postrenovation with the originating sod farm (Crouch et al, 2017). Bacterial 16S rRNA sequencing revealed that across all four lawns in the study, the Gram-negative, Proteobacteria phylum was 52.2-58.6% of the observed sequences, of which the genus Rhodoplanes was widely abundant (26.4-37.3%).…”
Section: Plant Species Compositionmentioning
confidence: 99%
“…Increased SOM if turf species are deeper rooting (Qian et al, 2010); specific turfgrass species differences in soil C, N, and SOM accumulation (Law et al, 2017); increased soil N retention and turf productivity with diverse turf systems (Thompson and Kao-Kniffin, 2016); the soil microbiome across different urban grasslands in the Mid-Atlantic region pre-and post-construction were more similar than different, but were enriched with copiotrophic bacteria (Crouch et al, 2017) Soil disturbances/cultivation May stimulate SOM mineralization due to soil aeration and degradation of soil aggregates, but SOM effects may be offset by improved plant growth (Murphy and Ebdon, 2013); soil disturbance does not appear to significantly alter the soil microbiome once adapted to typical lawn edaphic and management conditions (Yao et al, 2006;Bartlett et al, 2007;Shi et al, 2012;Crouch et al, 2017) These potential effects may vary by the intensity of each management practice, geographically, and under different management goals. This review and this table present preliminary attempts to link multiple management practices to different soil nutrient cycles via impacts on the soil microbiome.…”
Section: Irrigationmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of these microbial groups has motivated efforts to understand their ecology in global ecosystems and develop ways to manipulate their impacts on plants through management or plant breeding (Bakker, Manter, Sheflin, Weir, & Vivanco, ; Fierer, ; Walters et al, ). Despite the potential to leverage the microbial diversity in soil to influence plant growth, aside from work in turfgrass (Beirn et al, ; Crouch, Carter, Ismaiel, & Roberts, ), relatively little research has focused on plants that are cultivated for their ornamental traits.…”
Section: Introductionmentioning
confidence: 99%